Mice deficient for prion protein exhibit normal neuronal excitability and synaptic transmission in the hippocampus. - Lledo, P M (1996)
We recorded in the CA1 region from hippocampal slices of prion protein (PrP) gene knockout mice to investigate whether the loss of the normal form of prion protein (PrPC) affects neuronal excitability as well as synaptic transmission in the central nervous system. No deficit in synaptic inhibition was found using field potential recordings because (i) responses induced by stimulation in stratum radiatum consisted of a single population spike in PrP gene knockout mice similar to that recorded from control mice and (ii) the plot of field excitatory postsynaptic potential slope versus the population spike amplitude showed no difference between the two groups of mice. Intracellular recordings also failed to detect any difference in cell excitability and the reversal potential for inhibitory postsynaptic potentials. Analysis of the kinetics of inhibitory postsynaptic current revealed no modification. Finally, we examined whether synaptic plasticity was altered and found no difference in long-term potentiation between control and PrP gene knockout mice. On the basis of our findings, we propose that the loss of the normal form of prion protein does not alter the physiology of the CA1 region of the hippocampus.